Boron Doped Nanocrystalline Diamond/Reticulated Vitreous Carbon Composites Decorated with Silver Nanoparticles - Oishi, Silvia S.; Couto, Andrea B.; Botelho, Edson C. [UNESP]; Ferreira, Neideneî G. (Springer Nature, 2016)
Boron doped nanocrystalline diamond films (BDND) were grown on reticulated vitreous carbon (RVC) heat treated at 1000 and 1700 °C. Silver (Ag) nanoparticles were electrodeposited on RVC and RVC/BDND composites by potentiostatic reduction of AgNO3 solution. The samples were characterized by scanning electron microscopy, Raman spectroscopy, X-ray diffraction, and cyclic voltammetry. The samples conductivities influenced the Ag deposition amount as well as the Ag particle sizes where the smaller Ag particles were observed for RVC/BDND composites. The stability of Ag nanoparticles was also confirmed by cyclic voltammetry.
Keywords: Ag; diamond; electrodeposition